Foundations of mental health care - Valfre, Michelle Morrison (St. Louis, Mo. : Elsevier Mosby, 2005)
This comprehensive text provides a historical overview of mental health care, theoretical foundations, information on therapeutic skills, problems throughout the life cycle and psychological and psychosocial problems.
Includes bibliographical references (p. 371-377) and index.
Keywords: Psychiatric nursing; Mental health services; Mental Disorders -- therapy; Mental Disorders -- nursing